2013
DOI: 10.2967/jnumed.112.116921
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Early Response Evaluation of Locally Advanced Non–Small Cell Lung Cancer Treated with Concomitant Chemoradiotherapy

Abstract: The potential of 18 F-FDG PET changes was evaluated for prediction of response to concomitant chemoradiotherapy in patients with locally advanced non-small cell lung cancer (NSCLC). Methods: For 28 patients, 18 F-FDG PET was performed before treatment, at the end of the second week of treatment, and at 2 wk and 3 mo after the completion of treatment. Standardized uptake value (SUV), maximum SUV, metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were obtained. Early metabolic changes were defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 31 publications
2
71
2
1
Order By: Relevance
“…Therefore, in our study, we chose the change of lesion volume as the evaluation criteria. (2) Contrary to other studies (8,28), it seems that all changes in 18 F-RGD parameters (DSUV max , DT/NT, and DTV) have no close relationship to short-term outcome in this study. Perhaps this mostly depends on the influence from baseline parameters.…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, in our study, we chose the change of lesion volume as the evaluation criteria. (2) Contrary to other studies (8,28), it seems that all changes in 18 F-RGD parameters (DSUV max , DT/NT, and DTV) have no close relationship to short-term outcome in this study. Perhaps this mostly depends on the influence from baseline parameters.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies have also shown that preoperative staging PET/CT leads to change in the treatment planning and reduces the frequency of futile thoracotomies and the total number of thoracotomies (6,7). PET-based quantitative parameters have been proposed as reliable indicators of survival in patients with lung cancer in both pretreatment and posttreatment settings (8)(9)(10)(11)(12). In the posttherapy setting, several studies point to the usefulness of monitoring the treatment response based on decreased SUVs on serial 18 F-FDG PET imaging of the primary tumor (4,8).…”
mentioning
confidence: 99%
“…PET-based quantitative parameters have been proposed as reliable indicators of survival in patients with lung cancer in both pretreatment and posttreatment settings (8)(9)(10)(11)(12). In the posttherapy setting, several studies point to the usefulness of monitoring the treatment response based on decreased SUVs on serial 18 F-FDG PET imaging of the primary tumor (4,8). Higher volume of residual metabolically active tumor after definitive treatment appears to be associated with poorer survival (13,14).…”
mentioning
confidence: 99%
“…Van Elmpt et al (31) assessed 18 F-FDG PET uptake patterns before and 2 wk into therapy in 34 advanced-stage NSCLC patients and reported that a marked decrease in the 18 F-FDG PET signal between the two PET scans predicted higher overall survival. In a similar Dutch study, Usmanij et al (32) showed that a decrease in total-lesion glycolysis of more than 38% during the first 2 wk of therapy was associated with a significantly longer progression-free survival.…”
Section: Pet For Radiation Treatment Adaptation and Normal-tissue Chamentioning
confidence: 96%